Mesenchymal stem cells limit vascular and epithelial damage and restore the impermeability of the urothelium in chronic radiation cystitis - Clément Brossard; Anne-Laure Pouliet; Anne‐Charlotte Lefranc; Mohamedamine Benadjaoud; Morgane Dos Santos; Christelle Demarquay; Valerie Buard; Marc Benderitter; Jean-Marc Simon; Fabien Milliat; Alain Chapel (Stem Cell Research & Therapy, 2023)
Abstract Background Cellular therapy seems to be an innovative therapeutic alternative for which mesenchymal stem cells (MSCs) have been shown to be effective for interstitial and hemorrhagic cystitis. However, the action of MSCs on chronic radiation cystitis (CRC) remains to be demonstrated. The aim of this study was to set up a rat model of CRC and to evaluate the efficacy of MSCs and their mode of action. Methods CRC was induced by single-dose localized irradiation of the whole bladder using two beams guided by tomography in female Sprague–Dawley rat. A dose range of 20–80 Gy with follow-up 3–12 months after irradiation was used to characterize the dose effect and the kinetics of radiation cystitis in rats. For the treatment, the dose of 40 Gy was retained, and in order to potentiate the effect of the MSCs, MSCs were isolated from adipose tissue. After expansion, they were injected intravenously during the pre-chronic phase. Three injections of 5 million MSCs were administered every fortnight. Follow-up was performed for 12 months after irradiation. Results We observed that the intensity and frequency of hematuria are proportional to the irradiation dose, with a threshold at 40 Gy and the appearance of bleeding from 100 days post-irradiation. The MSCs reduced vascular damage as well as damage to the bladder epithelium. Conclusions These results are in favor of MSCs acting to limit progression of the chronic phase of radiation cystitis. MSC treatment may afford real hope for all patients suffering from chronic radiation cystitis resistant to conventional treatments.